Coal bottom ash as a sustainable supplementary cementitious material for the concrete exposed to seawater - Mangi, Sajjad Ali; Mohd Haziman, Wan Ibrahim; Norwati, Jamaluddin; Mohd Fadzil, Arshad; Memon, Sheeraz Ahmed; Shahiron, Shahidan; Putra Jaya, Ramadhansyah (AIP Publishing, 2019)
The performances of concrete construction exposed to seawater have been considered since long-time. It was generally perceived that the seawater effects could be decelerated by introducing supplementary cementitious materials (SCM) in concrete, which probably reduces its penetrability. Lower penetrability retains the aggressive slats out of the concrete, slows leaching of soluble materials such as lime, reduces the carbonation depth, and better corrosion protection to the reinforcement. Therefore, this study aims to evaluate the compressive strength performances of concrete with and without CBA exposed to seawater. In this study CBA was ground for 20 hours, to get particle fineness as comparable to the cement. Two types of concrete mixes were prepared; one is without ground CBA (M1) and another is with 10% of ground CBA (M2) as a SCM. Concrete cubes were prepared and immersed in normal water for 28 days, to get the desired strength. Afterward, samples were shifted in seawater. The specimens were evaluated for variation in compressive strength and change in weight under dual environments; normal water and seawater at 28, 56 and 90 days. It was experimentally determined that presence of CBA in concrete, raises the strength after 56 days. The strength of M2 concrete at 90 days, gives about 11.3% and 10.2% greater strength under normal water and seawater respectively as compared to M1 concrete. Hence, the CBA presence in concrete, reduces the penetration of aggressive salts, it is an indication of better durability performances of CBA concrete. The practical investigations concluded that the use of CBA as SCM improves the strength of concrete in normal water as well as in seawater environment.